Theory, Design, Fabrication And Testing Of Capacitive Pressure Transducer - Virachami, Moganadass (Universiti Sains Malaysia, 2005)
Transducers are predominantly used as sensors, because with a few exceptions, their efficiency of conversion is very low and to achieve a higher efficiency of conversion, transducers need to use the electrical signals to the amplifier. The piezoelectric device (pressure sensing) is also a useful transducer (can be used in either direction). Transducer use of piezoelectric crystals is mainly confined to the conversion between pressure waves in a liquid or gas and electrical AC signals. The conversion of energy from an electrical form into stress can be achieved by the magnetically cored solenoids. Pressure Transducer operates to convert the physical variable pressure into an electrical output signal that is proportional to the pressure measurement. The output supply is in form of current or voltage signals. Standard signals allow combining transducers, controllers, computers or stored program controllers (SPC) of different manufacturers without incurring any problem. The standardization simplifies both works as the manufacturers and also as the designer or any company operating instruments and plants. Capacitive Pressure Transducer operates as a pressure sensing device which senses the changes of capacitance according to the changes of pressure applied to the transducer. The measurement of these changes (output) is defined in form of voltage signal using a special measurement circuit is build out of operational amplifiers, resistors, capacitors and switch. The measurement results and conclusion of the project conducted on the capacitive pressure transducer is presented in the last part of this report together with design of the pressure transducer and the measurement circuit.